Arterial palmar arch occlusion in a woman with Raynaud's disease taking oral combined menopausal hormone therapy: A case report - Cristina Llaneza-Suarez; Montserrat Eiriz-Eirin; Placido Llaneza (Elsevier, 2020)
Patients with surgical menopause often present to their primary care provider with menopausal symptoms. Here we present an unusual case of palmar arch artery occlusion in a 55-year-old woman with primary Raynaudˈs disease taking oral combined menopausal hormone therapy after surgical menopause for endometriosis. She was successfully treated with intravenous infusion of prostaglandin E1 and nitroglycerin patches over two weeks. Menopausal hormone therapy was stopped and her vasomotor symptoms did not recur.